An Inquiry Into the Diverse Modes of Caring in Khayelitsha Wetlands Parks World of Many Worlds - Sibango, Asemahle (Environmental Humanities South, 2023)
The management and governance of wetlands in Cape Town is largely informed by economic, techno-scientific, and engineering approaches which are deeply rooted in discourses of “Earth mastery”. Earth mastery aims to command, predict, and control the Earth's natural processes to access ecosystem services to benefit humans. When wetland management is solely informed by logics of domination and extraction for humans, then other ways of knowing, being, being with, and caring for spaces such as the Khayelitsha Wetlands Park (KWP) are often overlooked and overshadowed. Using Maria Puig de la Bellacasa's (2011:90) work on ‘Matters of Care in Technoscience' where the notion of care is viewed as “an affective state, a material vital doing, and an ethico-political obligation”, this thesis draws attention to meanings, practices, and enactment of care through thinking with people and the more-than-human worlds in the KWP. Based on eight months of research in the KWP which involved looking at this space's associated landscapes and multispecies communities, this thesis explores ways of living with and relating to the KWP in Cape Town, South Africa, which do not subscribe to logics of domination. This is done by highlighting the often overshadowed and taken for granted forms of care and reciprocity that do not fall into the realm of the “advanced”, “technical”, and “objective” approaches in techno-scientific and engineering practices. In this thesis, I argue that people who live with urban wetlands practise their more-than-techno-scientific approaches and versions of care in these spaces. The evidence basis for these more-than-techno-scientific and more-than-engineering approaches of care are drawn from firstly, people's stories and experiences of relating to and living with the KWP and secondly, an analysis of care, coexistence, and co-becoming among more-than-human species in KWP. This thesis then suggests the importance of deconstructing and queering the understandings of care practices in wetland spaces by arguing that the government and institutions responsible for wetlands could draw on decolonial approaches in managing and practising care in these spaces, shifting from logics of control and domination to relational and historicised interactions with wetlands to address environmental injustices of the past and of the present. Queer theory is often associated with gender and sexuality where it means diverging from what is normalised, for instance, understanding that there are other ways of being outside heteronormative binaries. For this thesis I conceive queering beyond the context of gender and sexuality, for instance, I suggest the importance of being aware that KWP and wetlands in general host multiple worlds. Thus, governmental approaches of managing and caring for these waterbodies should not only conform to the techno-scientific and engineering notions of care. I suggest that these governmental approaches should be democratized and open a space to be informed by citizen science as well. They should understand that their approaches should not be a “one size fits all” as modes of being and of living differ from space to space. This thesis therefore uses the concept of queering as a way to suggest that techno-scientific governmental approaches of caring for wetlands must recognize the efforts of care that are practised by people and multispecies who live with these waterbodies and to start co-existing with them instead of overlooking and overshadowing them. This thesis, drew from the environmental humanities, environmental anthropology, and queer conceptual and theoretical schools of thought to achieve its purpose.